2012
DOI: 10.1001/archgenpsychiatry.2011.153
|View full text |Cite
|
Sign up to set email alerts
|

First-Time First-Trimester Induced Abortion and Risk of Readmission to a Psychiatric Hospital in Women With a History of Treated Mental Disorder

Abstract: Risk of readmission is similar before and after first-time first-trimester abortion, contrasting with a marked increased in risk of readmission post partum. We speculate that recent psychiatric episodes may influence women's decisions to have an induced abortion; however, this decision does not appear to influence the illness course in women with a history of treated mental disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
28
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 24 publications
2
28
0
Order By: Relevance
“…Childbirth was a more potent trigger for the early onset of severe bipolar episodes than termination. This finding is consistent with studies of induced abortion in the Danish registries . To our knowledge, however, this is the first study reporting rates of bipolar episodes after miscarriage.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Childbirth was a more potent trigger for the early onset of severe bipolar episodes than termination. This finding is consistent with studies of induced abortion in the Danish registries . To our knowledge, however, this is the first study reporting rates of bipolar episodes after miscarriage.…”
Section: Discussionsupporting
confidence: 91%
“…However, there is a paucity of studies that can inform women and their clinicians about the risk of a recurrence after a miscarriage or termination. Data from a Danish population‐based cohort showed that, although admission rates were high in women who had a termination, there was no evidence for an increased risk of readmission with bipolar disorder in the months following the induced abortion —rates were high before and following the procedure. There is less information regarding the impact of miscarriage on bipolar episodes, with data limited to small studies and case reports .…”
mentioning
confidence: 99%
“…It is not known how inaccuracy of mental health diagnoses or reporting of abortion influence the findings. Nevertheless, these findings support previous prospective research which has compared women who abort to women who give birth 2,30,31 . For instance, in a reanalysis of a sample from New Zealand, Fergusson and colleagues 30 found that, compared to women who gave birth to unwanted pregnancies, women who had abortions were not at a significant increased risk of subsequent anxiety disorders, depressive disorders, substance use disorders, and suicidal ideation when mental health at age 15, childhood adversities, and family environment were controlled in analyses.…”
Section: Discussionsupporting
confidence: 90%
“…For instance, in a reanalysis of a sample from New Zealand, Fergusson and colleagues 30 found that, compared to women who gave birth to unwanted pregnancies, women who had abortions were not at a significant increased risk of subsequent anxiety disorders, depressive disorders, substance use disorders, and suicidal ideation when mental health at age 15, childhood adversities, and family environment were controlled in analyses. In addition, research using Danish registries data has found support for the notion that mental health problems around the time of abortion are driven by factors other than the abortion 2,31 .…”
Section: Discussionmentioning
confidence: 99%
“…However, certain clinical features, including younger age at illness onset, family history of bipolar disorder, postpartum onset and the presence of manic features in the current episode of depression, suggested that she would be at risk for bipolar disorder. 3, 4 Treatment options include psychotherapy and pharmacotherapy. Psycho therapy is generally recommended for mild to moderate postpartum depression, whereas pharmacotherapy alone or in combination with psychotherapy is usually reserved for moderate to severe postpartum depression.…”
mentioning
confidence: 99%